Neuronal regulation of the stress response in C.elegans: Role of the neurotransmitter tyramine - de Rosa, Maria Jose (2014)
In nature, animals are frequently exposed to physiological and environmental challenges. The individual cellular response to these unfavorable conditions should be finely coordinated in multicellular organisms. The neural control of the systemic stress response was first evidenced in the free-living nematode C.elegans. However, the identity of the systemic neural signal that integrates stress perception with the response in non-neuronal tissues remains unknown. Our analysis of the C.elegans neuronal wiring diagram reveals that the circuits activated upon exposure to stressful situations converge in the only tyraminergic neuron, RIM. Tyramine is the invertebrate counterpart for adrenaline. Here we found that tyraminedeficient animals are resistant to thermal stress, starvation and pathogen infection. Moreover, these mutant strains exhibit molecular hallmarks of stressed worms, such as autophagy and lypolisis induction, even when they are grown under favorable conditions. Our results suggest that inhibition of the basal release of tyramine is a neuroendocrine signal required for a coordinated triggering of the stress response in C. elegans. This study contributes to a better understanding of the neurohormonal signaling that controls the systemic processes in multicellular organisms